Cytotoxicity Activity of Ethanol Extract of Andaliman Fruits (Zanthoxylum acanthopodium DC.) towards 4T1 Breast Cancer Cells - Rosidah, Rosidah; Hasibuan, Poppy Anjelisa Zaitun; Haro, Ginda; Satria, Denny (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Breast cancer is one of the world's leading cause of death in women. Due to the resistance of chemotherapeutic agents, there is a continuous need to search of natural products with anticancer activity. The use of natural products is expected to increase the effectiveness and decrease side effect. The purpose of this study was to investigate the anticancer activity of ethanol extract of andaliman fruits (EEAF) towards 4T1 cells. Extracts were prepared by maceration using solvent ethanol 96%. 4T1 cells were grown in culture medium DMEM then given by EEAF and doxorubicin. Cytotoxic test in vitro was done by MTT method [3-(4,5-dimetiltiazol-2-il) -2.5 difeniltetrazolium bromide] which is then analyzed using SPSS 21. The results from this study showed that the cytotoxic results (IC50) after treatment with EEAF and doxorubicin were 54.48 ± 0.22 µg/mL dan 0.80 ± 0.02 µg/mL.Based on the result above, we conclude that EEAF has cytotoxic activity towards 4T1 cancer cells. Key words: andaliman fruits, Zanthoxylum acanthopodium DC., ethanol extract, breast cancer, 4T1 cell line.